2017
DOI: 10.1089/acm.2015.0316
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Comparison of Emotional Freedom Technique and Cognitive-Behavioral Therapy to Reduce Adolescent Anxiety: A Pilot Study

Abstract: EFT is an efficacious intervention to significantly reduce anxiety for high-ability adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 60 publications
1
20
0
2
Order By: Relevance
“…In the study by Gaesser and Karan (2017) and studies currently underway, gifted students have reported effectively using EFT to address anxiety related to being in crowds, fear of failure and performing, generalized worry, and relieving their physical symptoms of anxiety (e.g., headaches, stomachaches, rapid breathing). In addition, they have shared that using EFT has helped them with feeling more confident approaching tasks and in social situations, falling asleep, concentrating, and completing homework.…”
Section: Eft Examples From the Fieldmentioning
confidence: 99%
“…In the study by Gaesser and Karan (2017) and studies currently underway, gifted students have reported effectively using EFT to address anxiety related to being in crowds, fear of failure and performing, generalized worry, and relieving their physical symptoms of anxiety (e.g., headaches, stomachaches, rapid breathing). In addition, they have shared that using EFT has helped them with feeling more confident approaching tasks and in social situations, falling asleep, concentrating, and completing homework.…”
Section: Eft Examples From the Fieldmentioning
confidence: 99%
“…Wells et al [50] found significant treatment effects after only one session of EFT when investigating subjects with specific phobia (diagnosed by means of the Diagnostic and Statistical Manual of Mental Disorders fourth edition - DSM-IV). So far, the description of possible Tapping treatment effects has mostly been restricted to behavioral data [50,51,52]. There are only few studies investigating electrophysiological correlates of EFT or its precursor Thought Field Therapy (TFT).…”
Section: Introductionmentioning
confidence: 99%
“…The emotional freedom technique is a safe, fast, reliable, and effective treatment for physical and psychological aspects (Bach et al, 2019;Gaesser & Karan, 2017). The emotional Freedom Technique is proof that one's health depends on the balance of energy in the body that flows throughout the body.…”
Section: Resultsmentioning
confidence: 99%